Comparison of methods for quantifying primordial follicles in the mouse ovary - Urooza C. Sarma; Amy L. Winship; Karla J. Hutt (BMC, 2020)
Abstract Background Accurate evaluation of primordial follicle numbers in mouse ovaries is an essential endpoint for studies investigating how endogenous and exogenous insults, such as maternal aging and chemotherapy, impact the ovarian reserve. In this study, we compared and contrasted two methods for counting healthy primordial follicles following exposure to cyclophosphamide (75 mg/kg), a well-established model of follicle depletion. The first was the fractionator/optical dissector technique, an unbiased, assumption-free stereological approach for quantification of primordial follicle numbers. While accurate, highly reproducible and sensitive, this method relies on specialist microscopy equipment and software, requires specific fixation, embedding and sectioning parameters to be followed, and is largely a manual process that is tedious and time-consuming. The second method was the more widely used serial section and direct count approach, which is relatively quick and easy. We also compared the impacts of different fixatives, embedding material and section thickness on the overall results for each method. Results Direct counts resulted in primordial follicle numbers that were significantly lower than those obtained by stereology, irrespective of fixation and embedding material. When applied to formalin fixed tissue, the direct count method did not detect differences in follicle numbers between saline and cyclophosphamide treated groups to the same degree of sensitivity as the gold standard stereology method (referred to as the Reference standard). However, when Bouin's fixative was used, direct counts and stereology were comparable in their ability to detect follicle depletion caused by cyclophosphamide. Conclusions This work indicates that the direct count method can produce similar results to stereology when Bouin's fixative is used instead of formalin. The findings presented here will assist others to select the most appropriate experimental approach for accurate follicle enumeration, depending on whether the primary objective of the study is to determine absolute primordial follicle numbers or relative differences between groups.